Effective Classroom Management in TEYL: Strategies, Challenges, and Practical Implications - Hardianti Hardianti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Effective classroom management is essential for successful teaching, particularly in Teaching English to Young Learners (TEYL), where structured, engaging environments foster academic achievement and social development. This study explores classroom management strategies, challenges, and adaptive practices employed by TEYL teachers. Using a qualitative research design, data were collected through semi-structured interviews with experienced teachers and analyzed using thematic analysis. The findings identified rules, routines, and positive reinforcement as key strategies for maintaining order and motivation in classrooms. Teachers also emphasized movement breaks and interactive activities as effective tools to manage diverse energy levels and sustain student engagement. Challenges, such as disruptive behaviors and resource constraints, were addressed through redirection techniques and tailored lesson plans, highlighting the importance of flexibility alongside consistency. Additionally, contextual and cultural factors influenced teachers’ approaches, underscoring the significance of culturally responsive practices. While the study provides valuable insights, limitations include reliance on self-reported data and the lack of classroom observations, which could offer further validation. These findings contribute to the growing body of knowledge on TEYL, offering practical recommendations for educators and policymakers to enhance classroom dynamics and learning outcomes.